THE EFFECT OF PRODUCT QUALITY AND PRICE ON THE MARKETING PERFORMANCE AT THE UMKM NAISHA MADU NUSANTARA IN BANGKINANG CITY - M. Ryan Rizaldi; Librina Tria Putri; Mustafa Kamal (Jurnal Riset Manajemen Indonesia, 2021)
Research to determine the effect of product quality and price on the marketing performance with simulthan and partial at the UMKM Naisha Madu Nusantara in Bangkinang City. Types and sources of data used in this study are primary data and secondary data, while data collection techniques used in this study were questionnaires, file research, observation and interviews. The population in this study were all consumers at the UMKM Naisha Madu Nusantara in 2019, amounting to 1.465consumers and based onn the Slovin formula it is know that the number of samples in this study is 100 consumers at the UMKM Naisha Madu Nusantara consisting of 50 consumers from the island of Sumatera, 30 consumers from the islan of Jawa and 20 consumers from Malaysia. The sample collection technique is using accidental sampling technique. Data analysis was performed using multiple linear regression models. Based on the simulthan and partial test results, the variable of product quality and price have a significant effect on the marketing performance at the UMKM Naisha Madu Nusantara in Bangkinang City. The closeness of the relationship that occurs between the atractiveness of product quality and price on the marketing performance is strong with a correlation coefficient R of 78,0%. While contribution of independent variables to the dependent variables is equual to 67,8% while the remaining 32,2% is influenced by other variables not examined in this study.